Clinical and genetic analysis of Noonan syndrome in 20 children - Ding, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To explore the clinical and genetic characteristics of Noonan syndrome in children. Methods: The clinical characteristics,genetic analysis and follow-up data of 20 children diagnosed with Noonan syndrome who were admitted to Department of Endocrinology, Genetics and Metabolism, Beijing Children's Hospital, Capital Medical University from March 2016 to December 2020 were retrospectively analyzed. Results: Among 20 children with Noonan syndrome, 13 were males and 7 were females. The age at diagnosis was 5.9 years (1.1 years to 12.2 years). The most common clinical complaints were delayed height growth, followed by hypospadias or cryptorchidism in 2 cases, and special facial appearance in 1 case. Physical examination revealed 12 cases of Noonan syndrome with facial features, 9 cases with cryptorchidism and hypospadias, 10 cases with abnormal cardiac structure, and 10 cases with mental retardation; Twelve patients were detected with PTPN11 variations, 4 patients carried SOS2 variations, 2 cases were confirmed with variations in SHOC2 and SOS1. Six children received recombinant human growth hormone treatment, and their height increased by 4.0 (2.5-6.0) cm to varying degrees at 9 months. No adverse events occurred. Conclusions: Male Noonan syndrome is more frequently found with external genitalia. In addition to the high frequency of PTPN11 variation, the frequency of gene variation in SOS2 gene is higher than previously reported. All of the SOS2 variations are de novo. The syndrome phenotype profiles could vary with the admitted clinical departments. To understand the full picture of the syndrome, it is necessary to collect medical information from different departments